Location Based Service for Information Publication Using GPS on Android-Based Mobile Phone - Ahmad Fali Okilas; Sri Desy Siswanti; M. Dieka Rachman (IAES Indonesia Section, 2014)
The increasing development of mobile technology makes some technology capable to running on multiple mobile platforms. One of them is Location Based Service. Location Based Service is a service provided by the position of the user. One of the utilization of Location Based Service technology is a publication of public information. This information may include important information such as hotels, gas stations, ATMs, and Event. Location Based Service is very dependent on the user's position, therefore, the accuracy of component positioning should be accurate enough. By default configurations android GPS accuracy is not very good, needed tweaking to minimize errors in accuracy. To measure the accuracy shift used haversine formula. Haversine formula is a method to measure the distance between two points on the sphere based on its latitude and longitude. Based on test results without tweaking the maximum accuracy shift is 30 meters while with tweaking only 11 meters. Average accuracy shift without tweaking is 18 meters down to 8 meters using tweaking. Thus the process of tweaking can improve the accuracy of GPS.